2016
DOI: 10.7717/peerj.2750
|View full text |Cite
|
Sign up to set email alerts
|

A retrospective study: cardiac MRI of fulminant myocarditis in children—can we evaluate the short-term outcomes?

Abstract: BackgroundFulminant myocarditis (FM) is an inflammatory disease of the myocardium that results in ventricular systolic dysfunction and causes acute-onset heart failure. Cardiac magnetic resonance (CMR) has become the primary noninvasive tool for the diagnosis and evaluation of myocarditis. The aim of our study was to assess the CMR findings at different course of FM and the short-term outcomes of fulminant myocarditis (FM) in children.MethodsEight FM children with CMR examinations were included in our study. I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 40 publications
0
4
0
1
Order By: Relevance
“…Cardiac troponin, CKMB, and CRP levels are all indicators of a possible myocardial injury. Currently, MRI is considered the gold standard due to its noninvasive utility in diagnosing and evaluating myocarditis in children [6]. e Lake Louise criteria were formulated in 2009. e requirements describe the findings on contrastenhanced MRI, increasing the sensitivity and specificity for the diagnosis of myocarditis.…”
Section: Discussionmentioning
confidence: 99%
“…Cardiac troponin, CKMB, and CRP levels are all indicators of a possible myocardial injury. Currently, MRI is considered the gold standard due to its noninvasive utility in diagnosing and evaluating myocarditis in children [6]. e Lake Louise criteria were formulated in 2009. e requirements describe the findings on contrastenhanced MRI, increasing the sensitivity and specificity for the diagnosis of myocarditis.…”
Section: Discussionmentioning
confidence: 99%
“…Currently, cardiac magnetic resonance (CMR) has become the primary noninvasive tool for the diagnosis and evaluation of myocarditis. [35] It provides good accuracy in measurement of LVEF, LVEDd, LVPWd, and IVSd. [36] We should focus on differences between FM and NFM using CMR in further studies.…”
Section: Discussionmentioning
confidence: 99%
“…We found that the sensitivity of CMR was different between the acute phase and the recovery phase: T2WI sensitivity was 75 and 50%, respectively, in the acute phase and the recovery phase, and LGE sensitivity was 75 and 62.5%, respectively, in the acute phase and the recovery phase, suggesting that myocardial edema began to resolve 14 days after onset while LGE was relatively delayed. In 2016, Wang et al performed an early CMR examination and short-term follow-up of 8 children with AFM (22). It was found that CMR has certain value for the early diagnosis and short-term follow-up of children with AFM.…”
Section: Discussionmentioning
confidence: 99%